DNA Transposon Expansion is Associated with Genome Size Increase in Mudminnows. (1st October 2021) - Lehmann, Robert; Kovařík, Aleš; Ocalewicz, Konrad; Kirtiklis, Lech; Zuccolo, Andrea; Tegner, Jesper N; Wanzenböck, Josef; Bernatchez, Louis; Lamatsch, Dunja K; Symonová, Radka
Abstract: Genome sizes of eukaryotic organisms vary substantially, with whole-genome duplications (WGD) and transposable element expansion acting as main drivers for rapid genome size increase. The two North American mudminnows, Umbra limi and Umbra pygmaea, feature genomes about twice the size of their sister lineage Esocidae (e.g., pikes and pickerels). However, it is unknown whether all Umbra species share this genome expansion and which causal mechanisms drive this expansion. Using flow cytometry, we find that the genome of the European mudminnow is expanded similarly to both North American species, ranging between 4.5 and 5.4 pg per diploid nucleus. Observed blocks of interstitially located telomeric repeats in U. limi suggest frequent Robertsonian rearrangements in its history. Comparative analyses of transcriptome and genome assemblies show that the genome expansion in Umbra is driven by the expansion of DNA transposon and unclassified repeat sequences without WGD. Furthermore, we find a substantial ongoing expansion of repeat sequences in the Alaska blackfish Dallia pectoralis, the closest relative to the family Umbridae, which might mark the beginning of a similar genome expansion. Our study suggests that the genome expansion in mudminnows, driven mainly by transposon expansion, but not WGD, occurred before the separation into the American and European lineage.